International and Comparative Studies in Adult and Continuing Education - Egetenmeyer, Regina; Boffo, Vanna; Kröner, Stefanie (Studies on Adult Learning and Education, 2020)
This volume gives theoretical and practical insights in international and comparative research in the field of adult and continuing education. The 16 contributions of this volume give three perspectives on international and comparative adult education. The first perspective focuses on the question how internationalisation and comparative adult and continuing education can be taught. The second perspective gives insights into the results of comparative research that has been conducted throughout a two-week Winter School that took place in February 2019 in Würzburg. The third perspective complements the two perspectives with insights into international projects and practices in adult and continuing education. The authors of this volume are contributing to the transnational Winter School International and comparative studies in adult and continuing education in Würzburg, Germany since 2014.